Effectiveness of bioinoculants bacillus cereus and Trichoderma asperellum as oil palm seedlings growth promoters - Tuan Muhammad Syafiq, Tuan Hassan; Syd Ali, Nusaibah; Rafii, Mohd Yusop (Universiti Putra Malaysia Press, 2021)
In the establishment of oil palm seedlings, apart from the application of adequate amount of fertilizers, other sustainable plant nutrient sources are known to have the potential in enhancing vegetative growth and improve plants’ resistance against pests and diseases. The application of plant growth promoters is known to contribute towards sustaining healthy plant growth leading to strong plant defense mechanisms. The present study was conducted to determine plant growth promotion potentials of bacterium, Bacillus cereus (UPM15) and fungus Trichoderma asperellum (UPM16). Isolates B. cereus and T. asperellum were assessed on their effectiveness as plant growth promoters for oil palm seedlings. Plant growth-promoting potentials were evaluated in terms of their ability to produce indole acetic acid (IAA), a naturally occurring plant hormone of the auxin class, iron-chelating compounds or siderophores, and phosphate solubilisation, considered to be one of the most important traits associated with plant phosphate nutrition. A series of treatments was applied to establish the potential of B. cereus and T. asperellum as microbial inoculants in singles and mixed applications in an in vivo nursery study. The ability to solubilize precipitated phosphate and to produce siderophores was positively demonstrated by T. asperellum. Both B. cereus and T. asperellum were capable of producing IAA. The results showed that the former significantly contributed towards growth enhancement of roots and the later in growth promotion of aerial parts of oil palm seedlings. Mixture of these isolates yielded good vegetative growth. The study revealed the benefits of microbial inoculants that extended beyond their capacity as biofertilizers.